Prevalensi dan Intensitas Tungau Parasit pada Kucing Peliharaan yang Diperiksakan di beberapa Klinik Hewan Purwokerto - Amelia Nurma Hidayah; Bambang Heru Budianto; Hery Pratiknyo (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2022)
This study aimed to determine the prevalence and intensity of parasitic mites in domestic cats at several veterinary clinics in Purwokerto. This research was conducted by cross sectional method using random sampling technique at three veterinary clinics in Purwokerto City. The identification of parasitic mites was analyzed descriptively, the data on the mites found were then analyzed using the prevalence and intensity formulas. The prevalence and intensity figures obtained were then compared with the prevalence and intensity category tables. The results of the study reported that the total prevalence of parasitic mites was 85%, which was included in the category of prevalence usually with moderate infestation, with a total intensity of parasitic mites of 196.7 which included in the category of very severe intensity. Species of parasitic mites found include Otodectes cynotis, Notoedres cati and Lynxacarus radovskyi.